1977
DOI: 10.2134/agronj1977.00021962006900040003x
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of Increasing Tropical Rice Production through Ratooning1

Abstract: Production of a rice (Oryza sativa L.) crop by ratooning is feasible under some conditions. Ratooning of rice eliminates two labor‐saving operations: raising seedlings in the seedbed and transplanting in the main field. Field experiments were conducted for 2 years on Maahas clay (an isothermic clayey mixed Aquic Tropudalf) to evaluate the performance of rice cultivars for ratooning ability and the agronomic practices that affect ratooning. The agronomic practices studied were cutting height of the crop produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 1 publication
5
32
0
4
Order By: Relevance
“…Entre os fatores ambientais que afetam o crescimento e desenvolvimento das plantas, a temperatura e a luz são os de maior influência no comportamento da soca, particularmente no perfilhamento (De Datta & Bernasor, 1988). A redução do número de perfilhos férteis da soca com a antecipação do reinício da inundação após a colheita somente foi verificada por Bahar & De Datta (1977), quando as plantas da cultura principal foram cortadas ao nível do solo. Contudo, quando o corte foi feito a 15 cm de altura, o tempo de reinício da irrigação não afetou o número de perfilhos, nem a produtividade da soca.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Entre os fatores ambientais que afetam o crescimento e desenvolvimento das plantas, a temperatura e a luz são os de maior influência no comportamento da soca, particularmente no perfilhamento (De Datta & Bernasor, 1988). A redução do número de perfilhos férteis da soca com a antecipação do reinício da inundação após a colheita somente foi verificada por Bahar & De Datta (1977), quando as plantas da cultura principal foram cortadas ao nível do solo. Contudo, quando o corte foi feito a 15 cm de altura, o tempo de reinício da irrigação não afetou o número de perfilhos, nem a produtividade da soca.…”
Section: Resultsunclassified
“…O manejo da água antes e após a colheita da cultura principal afeta a capacidade produtiva da soca (Prashar, 1970a(Prashar, , 1970bVotong, 1975;Bahar & De Datta, 1977;Nadal & Carangal, 1979). A disponibilidade de água, isoladamente, não garante êxito na produção da soca; é necessário, também, que haja água disponível para o cultivo na época adequada.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Plowing followed by harrowing of the main crop land gave higher grain yield and panicle number in ratoon plants compared to main crop grown under zero tillage. Bahar and De Datta (1977) observed that the total rice grain yields were 11.7, 11.4 and 7.6 t ha -1 for transplanted, transplanted-direct seeded and transplanted ratooned cropping system and usual land preparation involving plowing followed by harrowing to main crop produced more tillers in the ratoon crop compared to zero tillage. Parago (1963b) concluded that success of the ratoon crop is dependent principally on the thorough preparation of land for the main crop and decreased viability of ratoon was noticed with increase in plowing depth even though there was increase in elongation of culm, however, an increase of the number of panicles per plant was observed and plowing 25 cm deeper recorded higher grain yield compared to shallow tillage.…”
Section: Land Preparationmentioning
confidence: 98%
“…Ratoon plants grown after zero tillage yielded least, while plowing deeper increased culm elongation and panicles per plant, and plowing 25 cm deep gave higher grain yield than shallow tillage, however, plowing deeper than 25 cm tended to decrease ratoon crop viability (Hsieh et al, 1968;De Datta and Bernasor, 1988). The main crop that had been plowed and harrowed produced the highest (1.1 t ha -1 ) ratoon crop yield (Bahar and De Datta, 1977). Further, De Datta and Bernasor (1988) reported good ratoon yields from drilled crops.…”
Section: Land Preparationmentioning
confidence: 99%